ANALISIS PENGARUH DIFERENSIASI PRODUK DAN PREFERENSI MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA KEDAI KOPI MULO DI TIMIKA - Miranda Merpati Rombe; Yuliana Wearbitu, Stepanu Sandy (CV. ADIBA AISHA AMIRA, 2024)
This study aims to determine the analysis of the effect of product differentiation and brand preference on purchasing decisions at mulo coffee shops in Timika. The method used by researchers is associative. The data collection technique used by researchers is to distribute questionnaires to 100 respondents. The analytical tool used in this research is SPSS. The results showed that product differentiation had a negative and significant effect on purchasing decisions at mulo coffee shops and brand preference had a positive and significant effect on purchasing decisions at mulo coffee shops